Awareness and Attitudes of Pregnant Women Regarding Endocrine Disruptors - MİRAL, MUKADDES TURAN; KOÇ, ELİF (Womens Health & Action Research Centre, 2025)
This study aims assessment of the level of knowledge and attitudes of pregnant women regarding endocrine disruptors. This crosssectional, descriptive study was carried out in the antenatal clinic of a hospital in Istanbul between January 25, 2023, and March 3, 2023. The study sample consisted of 350 pregnant women. The data collection tools were a Personal Data Form, an Endocrine Disruptors Awareness Test, and an Endocrine Disruptors Attitude Scale. The rate of women reporting that they received no education on endocrine disruptors is 99.7%. The average score for the Endocrine Disruptors Awareness Test was 9.15 +/- 3.19, and for the Endocrine Disruptors Attitude Scale was 73.26 +/- 8.51. There was a moderate positive correlation between the scores of the Endocrine Disruptors Awareness Test and the Endocrine Disruptors Attitude Scale (r= .52, p< .01). In conclusion, it is believed that pregnant women may be aware of toxic substances in their environment but may not recognise them as endocrine disruptors. It is recommended that the topic of endocrine disruptors be added to antenatal education.
Keywords: Attitude; Endocrine Disruptors; Pregnant; Knowledge